Feasibility of internal standardization in the direct and simultaneous determination of As, Cu and Pb in sugar-cane spirits by graphite furnace atomic absorption spectrometry - Caldas, Naise Mary [UNESP]; Oliveira, Silvana Ruella [UNESP]; Gomes Neto, José Anchieta [UNESP] (Elsevier B.V., 2009)
Bismuth and Sb were evaluated as internal standards (IS) to minimize matrix effects on the direct and Simultaneous determination of As, Cu, and Pb in cachaca by graphite furnace atomic absorption spectrometry using W-coated platform plus Pd center dot Mg(NO(3))(2) as modifier. For 20 mu L injected sample, calibration within the 0.5-10 mu g L(-1) As, 100-1000 mu g L(-1) Cu and 0.5-30 mu g L(-1) Pb intervals were established using the ratios As absorbance to SI) absorbance, Cu absorbance to Bi absorbance and Pb absorbance to Bi absorbance versus analytes concentration, respectively. Typical linear correlations of 0.998, 0.999 and 0.999 were, respectively. obtained. The proposed method was applied for direct determination of As, Cu and Pb in 10 commercial cachaca samples and results were in agreement with those obtained by inductively coupled plasma mass spectrometry at 95% confidence level. The found characteristic masses were 30 pg As, 274 pg Cu and 39 pg Pb. The useful lifetime of the graphite tube was around 760 firings, Recoveries of As, Cu and Pb added to cachaca samples varied, respectively, from 98% to 109%, 97% to 108% and 98'. to 104% with internal standards and from 48% to 54%, 53% to 92% and 62% to 97% without internal standards. The limits of detection were 0.13 mu g L(-1) As, 22 mu g L(-1) Cu and 0.05 mu g L(-1) Pb. The relative standard deviations (n = 12) for a spiked sample containing 20 mu g L(-1). As. Pb and 500 mu g L(-1) Cu were 1.6%, 1.0%, and 1.8% with IS and 4.3%, 5.2%, and 5.5% without IS. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Arsenic; Copper; Lead; Cachaca; Internal standardization; Graphite furnace atomic absorption spectrometry